POSITIVE EFFECT OF ANDRODOZ COMPLEX ON THE QUALITY OF SEMINAL PLASMA’S - A. Yu. Tsukanov; A. S. Delitsin (Андрология и генитальная хирургия, 2017)
Background. The problem of male infertility has a large proportion of patient treatment to andrologyst. The quality of seminal plasma affects the result of successful conception. We investigated in a detail a positive effect of Androdoz complex on a change of semen’s parameters. Objective is to study in a detail the changes in indications of seminal plasma after applications of Androdoz complex.Materials and methods. 62 patients were included in a study (middle age 28,4 ± 2,3). The patients were divided into 2 groups. Men group 1 (n = 33) received AndroDoz complex (2 capsules 2 times a day for 30 days). Men group 2 (n = 29) received L-сarnitine (150 mg 2 times a day for 30 days). All patients were examined according to the recommendations of the Russian Society of Urologists, and biochemical analysis of ejaculate was performed before the drugs» appointment.Results. In Group 1 obtained statistically significant differences in terms of: the volume of ejaculate, the level of fructose, citrate and zinc. In group 2 the changes were not statistically significant.Conclusion. Thus, the use of AndroDoz complex significant positive effect on the quality of the seminal plasma.